The importance of previous season performance on world-class 200- and 400-m individual medley swimming - Del Castillo, Jose A; González Ravé, José María; Hermosilla, Francisco; Santos del Cerro, Jesús; Pyne, David B. (My University, 2021)
: We examined the degree to which 200-m and 400-m Individual Medley (IM) performance was related to sprint-, middle- and long-distance events before a swimmer reached a Top-20 world ranking. A retrospective longitudinal modelling study was conducted. Data on Top-20 swimmers between 2010 and 2018 were obtained from publicly available websites. A general linear model was used to examine associations between 200-m and 400-mIM performance (FINA ranking points) and performance in sprint, middle-distance and distance events in the previous two years. In the 200-mIM, there were significant associations (p < 0.001) between prior competition results obtained for both the 200-mIM (r = 0.80; ¿ = 0.543) and 400-m IM (r = 0.70; ¿ = 0.317) events before the Top-20 performance in 200-mIM in the year of the Top-20. Sprint distance events were associated (p < 0.006; r = 0.39; ¿ = 0.088) with 200-mIM (t). Each additional 10 FINA points in the 200-mIM in each of the two years preceding the Top-20 performance. were associated with an increase of 5 FINA points in 200-mIM in in the year of the Top-20 (goodness of fit R2 = 0.70). There were similar associations (p < 0.001) for a Top 20-FINA 400-mIM performance with both 200-mIM (r = 0.72; ¿ = 0.385) and 400-m IM (r = 0.79; ¿ = 0.492) events in the two years before a swimmer reached the Top 20. Middle-distance events were associated with 400-mIM performance (p < 0.001; r = 0.53; ¿ = 0.163). Each additional 10 FINA points in 400-mIM in in each of the two years preceding the Top-20 performance were associated with an increase of 5 FINA points in in the year that a swimmer reached the Top-20 (goodness of fit R2 = 0.75). The specificity and complexity of the IM require a thorough preparation in this event for world class performances. The 200-mIM is more closely related to sprint distance events, whereas middle-distance events support preparations for the 400-mIM